NEGATIVE CORRELATION OF DIFFERENCE FORMULATION ON LEGAL STANDING IMPLEMENTATION OF JUDICAL REVIEW IN THE SUPREME COURT - Kartono Kartono (Jurnal Dinamika Hukum, 2016)
Legal certainty in the form of legislation, among others, can be shown by the consistency of the formulation of legal norms with the sub ordinate regulations. Therefore, the study on the influence of different formulations of the norm in the implementation of the law needs to be done. Evidently, the different formulations of the norm of the applicant's position as a legal entity has the right to a judicial review against the decision of a negative correlation, ie, the emergence of disparity in the results of the trials. Event rigger rejection of either party litigants.Keywords: Judicial Review, Legal Certainty, the Supreme Court